African Human Rights Law Reports 2007 - Edited by The African Commssion on Human and Peoples' Rights & the Centre for Human Rights, University of Pretoria (Pretoria University Law Press (PULP), 2008)
African Human Rights Law Reports 2007 Edited by The African Commssion on Human and Peoples' Rights & the Centre for Human Rights, University of Pretoria 2008 ISSN: 1812-2418 Pages: xxxiii 197 Print version: Available Electronic version: Free PDF available